GAMBARAN KEJADIAN WANITA DENGAN DOUBLE BURDEN DI KABUPATEN BANGKALAN - aim matun nadhiroh; Yunita Fitroh Aulani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Double burden (double loading) is a form of gender discrimination that occurs in a woman in the division of roles, when the women have two roles as housewives and career women. The purpose of this study is to describe of women with a have double burden.Design research using descriptive method with sampling technique is simple random sampling. Sample in this study were all married women, have husband and children in Perumahan Daerah (PERUMDA) RT / OO1 / RW / 003Mlajah Village Bangkalan with a total population 73 women and a sample of 61 women. The variable in this study was the occurrence of double burden. Data collection instrument used primary and secondary data by using the data questionnaire. Data processing used editing, coding, scoring and tabulating steps.The result showed that the majority of women who do not have a double burden are 49 women (80,3 %) andwomen who have double burden are 12 women (19,7%).Therefore, women are expected to be able to divide time (time management) to perform the role as housewivesand career women. Career women are also responsible for housekeeping. Women with working hours which does not exceed the time limit set by labor department (DEPNAKER) ranging from 7-8 hours per day. Women who work beyondthe working hours that have been determined by DEPNAKER, means they are in the overtime.